Development and validation of novel PCR primers for identification of plasmid-mediated colistin resistance (mcr) genes in various environmental settings - Gorecki, Adrian (2021)
Antibiotic resistance is considered one of the biggest threats to public health and has become a major concern for governments and international organizations. Combating this problem starts with improving global surveillance of antibiotic resistance genes (ARGs) and applying standardized protocols, both in a clinical and environmental context, in agreement with the One Health approach. Exceptional efforts should be directed to controlling ARGs conferring resistance to Critically Important Antimicrobials (CIA). In this study, a systematic literature review to synthesize data on the identification of mcr genes using a PCR technique was performed. Additionally, a novel set of PCR primers for mcr-1 – mcr-9 genes detection was proposed. The developed primers were in silico and experimentally validated by comparison with mcr-specific PCR primers reported in the literature. This validation, besides being a proof-of-concept for primers’ usefulness, provided insight into the distribution of mcr genes in municipal wastewater, clay and river sediments, glacier moraine, manure, seagulls and auks feces and daphnids from four countries. This analysis proved that commonly used primers may deliver false results, and some mcr genes may be overlooked in tested samples. Newly-developed PCR primers turned out to be relevant for the screening of mcr genes in various environments.